A qualitative pilot study of the virtual implementation of the WHO caregiver skills training program in Brazil - Rauen, Camila Cardoso; de Fátima Minneto, Maria; Santos, Letícia Pascelli; Nogara, Karime Haviaras; Matos, Elyse Bacila; da Silva, Ana Paula Wasilewski; de Oliveira, Eduardo Cassanho; Salvador, Ana Paula Viezzer; Dória, Gustavo Manoel Schier (Frontiers in Education, 2025)
IntroductionCaregiver Skills Training (CST) is an evidence-based program developed by the World Health Organization (WHO) which aims to equip caregivers with skills to support children with neurodevelopmental disorders and enhance their wellbeing, particularly in low-resource settings. The COVID-19 pandemic affected CST implementation in Brazil, necessitating adaptations for remote delivery.MethodsThis qualitative study evaluated the acceptability, feasibility, and perceived effectiveness of a remote CST pilot implementation in Brazil. Focus groups were conducted with four master trainers (MTs), 11 facilitators, and 26 caregivers. The data were analyzed using Content Analysis and Descending Hierarchical Classification (IraMuTeQ®).ResultsSix thematic categories emerged from MTs, five from facilitators, and six from caregivers. Remote CST was well-received, enhancing caregiver learning, improving perceptions of children’s challenges, and facilitating modifications in family routines.DiscussionChallenges identified included technological barriers, caregiver overload, lack of bonds between caregivers, and the need for practical training for facilitators. Engagement varied according to profile, affected by psychosocial and economic vulnerabilities. Participants valued the content and resources of the training, suggesting few adjustments. The importance of exchanges between families and the support of professionals was highlighted. A change in understanding the child’s difficulties, learning strategies and empowerment of caregivers was observed.ConclusionCST implementation in Brazil highlights the crucial role of caregiver training and the importance of cultural adaptation, demonstrating the program’s potential to expand access to structured interventions for families of children with neurodevelopmental disorders.